2013
DOI: 10.3390/s131013063
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Sensitive Detection of Pb2+ in Foods Using Disposable Screen-Printed Electrode Modified by Reduced Graphene Oxide

Abstract: In this study, reduced graphene oxide (rGO) was electrochemically deposited on the surface of screen-printed carbon electrodes (SPCE) to prepare a disposable sensor for fast detection of Pb2+ in foods. The SEM images showed that the rGO was homogeneously deposited onto the electrode surface with a wrinkled nanostructure, which provided 2D bridges for electron transport and a larger active area for Pb2+ adsorption. Results showed that rGO modification enhanced the activity of the electrode surface, and signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 21 publications
1
24
0
1
Order By: Relevance
“…5. The reduction potential of −0.6 eV, obtained for Pb 2+ with the printed sensor, is comparable to reported literature values [43]. These results indicated that the sensor only provided a response when brought in contact with Pb 2+ , however, no response was detected when the sensor was brought in contact with Hg 2+ ions.…”
Section: Resultssupporting
confidence: 93%
“…5. The reduction potential of −0.6 eV, obtained for Pb 2+ with the printed sensor, is comparable to reported literature values [43]. These results indicated that the sensor only provided a response when brought in contact with Pb 2+ , however, no response was detected when the sensor was brought in contact with Hg 2+ ions.…”
Section: Resultssupporting
confidence: 93%
“…Graphene possesses unique optical, electrical, and thermal conductivity properties, as well as ultra‐thinness, and flexibility that makes graphene and its derivatives attractive for use in numerous areas of industry and biomedicine. Proposed uses for graphene‐based materials include molecular biosensors (Jian et al, ; Yan et al, ), bacterial detectors and antimicrobial surface treatments (Hu et al, ; Mannoor et al, ), filters for water purification (Subramani & Jacangelo ; Surwade et al, ), modifying gas barriers and adhesives for use in food packaging (Hu et al, ; Xiang et al, ), and wound dressing materials that promote accelerated healing (Fan et al, ; Lu et al, ). Also, graphene derivatives are potentially useful as components of medical implants (Lahiri et al, ; Aryaei et al, ), drug delivery platforms (Ma et al, ; Saeed et al, ), photothermal therapies (Qin et al, ; Nedosekin et al, ), and as scaffolding for tissue regeneration/engineering (Mahmood et al, ; Elkhenany et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…1). The cathodic current peak at −1.4 V is due to the irreversible electrochemical reduction of several oxygen-containing functional groups on the surface of GO [31]. A decrease in the reduction peak with increasing CV scans to almost a disappearing state confirms a near completion of the reduction of GO to rGO, as evident in Fig.…”
Section: Preparation Of the Bio-spcementioning
confidence: 61%